The Role of Learning on Insect and Spider Sexual Behaviors, Sexual Trait Evolution, and Speciation - Dion, Emilie; Monteiro, Antónia; Nieberding, Caroline M. (Frontiers in Ecology and Evolution, 2019)
We review experimental and theoretical evidence that learning in insects and spiders affects the expression of mate preferences and of sexual signals, the evolution of both traits, and ultimately patterns of assortative mating and speciation. Both males and females can modify their sexual preferences and signaling based on previous social interactions or the experience of visual, olfactory, gustatory, or auditory signals. Learning takes place during an early life exposure, previous personal sexual experiences or by observing the choices of others, and it can occur sometimes via very short (a few seconds) exposures to individuals or signals. We briefly review some of the molecular mechanisms that mediate learning in insects, as well as theoretical work that assesses how learning impacts the evolution of insect sexual traits and speciation. We suggest that future research should attempt to provide evidence of the adaptive nature of learning, which remains scarce in insects as well as in vertebrates, and explore further the mechanisms of learning in order to probe into their possible transgenerational inheritance. Future studies should also model how this process might further affect the evolution of sexual traits, and provide a unifying terminology for the underlying mechanisms of learning across diverse life-history contexts.